Domesticating international legal instruments in Malaysia: the challenges and prospects relating to anti human trafficking law - Mokhtar, Khairil Azmin; Ab Hamid, Zuraini (2014)
The international framework of human trafficking has becomes the main guiding framework for most of the countries around the globe in combating the crime. The issue of human trafficking was brought to global attention mainly through United Nations Universal Declaration of Human Rights 1948 (UDHR) followed by Protocol to Prevent, Suppress and Punish Trafficking in Persons especially Women and Children. It is the objective of UDHR to recognize the inherent dignity, equality and inalienable rights of a man which become the basis of freedom, justice and peace regardless the gender, race and religion of the person. The UN Protocol has supplemented the Declaration by providing a standard approach to state parties in combating the trafficking. It is known as “3Ps” model which aim to prevent the crime, protect the victim and prosecute the perpetrator. This paper provide legal analyses to determine whether the Malaysia’s legal response through its’ Anti Trafficking in Persons and Smuggling of Migrants Act 2007 and other supplemented Acts are in compliance with the UN Declaration and Protocol. It is an important area of study because the most recent U. S Department of Trafficking in Persons’ report shows that Malaysia has lack of “3Ps”approaches in its legal framework. This paper concludes that a reformation to Malaysia’s legal response is significant to ensure its compliance with the international framework and to be more successful in combating the crime.